The role of small antelope in ecosystem functioning in the Matobo Hills, Zimbabwe - Lunt, Nicola (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
The 28-month study assessed the impacts of five syntopic medium-sized mammalian browsers and one fire event in a woodland savanna in the Matobo Hills, Zimbabwe. Aspects of herbivory, mechanical pressures, seed dispersal and nutrient cycling were investigated for three species of small antelope (common duiker [Sylvicapra grimmia]1, klipspringer [Oreotragus oreotragus] and steenbok [Raphicerus campestris]) and two medium-sized species (bushbuck [Tragelaphus scriptus] and greater kudu [T. strepsiceros]). Focusing on Burkea africana2 woodland, in a system that does not include elephant (Loxodonta africana), effects of browsing antelope on woody and herbaceous vegetation development were investigated using exclusion plots. Browsers regulated woody plant cover (measured as basal stem area), with smaller antelope having a greater impact than larger species. This was linked to feeding height, feeding selectivity and mechanical pressures (e.g. twig breakage and trampling). Fire caused an initial reduction in above-ground standing biomass, but in the presence of fauna, pre-fire equilibria were attained within 15 months. In antelope exclosures, herbaceous biomass increased and woody biomass decreased following fire. Responses by woody vegetation to browsing varied among species, with highly palatable species typically exhibiting compensatory regrowth. Woody species richness and abundance (especially of palatable species) increased in the absence of browsers, but species richness of the herbaceous layer was promoted by moderate disturbance (trampling or fire). Faecal deposition behaviour, primarily the use of latrines by small antelope, resulted in localised soil enrichment within defended territories. Decomposition rates (and therefore return of nutrients to the soil) varied among species and seasons, due to defecation site selection, accessibility to decomposers and desiccation rates of faecal pellets. Controlled seed germination experiments indicated that ingestion by small antelope enhances germination rates of large, hard-seeded fruits such as Sclerocarya birrea. However, germination of savanna seeds may require multiple cues. This study demonstrated the critical roles of small antelope in ecosystem functioning, and highlights the importance of the less visible impacts of frequently overlooked smaller mammalian herbivores. Perturbations to the faunal community, especially small antelope, are predicted to have substantial impacts on woody plant cover.
Keywords: Antelopes -- Zimbabwe -- Rhodes Matopos National Park; Ecosystem health -- Zimbabwe -- Rhodes Matopos National Park; Forest ecology -- Zimbabwe -- Rhodes Matopos National Park; Savanna ecology -- Zimbabwe -- Rhodes Matopos National Park; Woody plants -- Effect of fires on -- Zimbabwe -- Rhodes Matopos National Park; Duikers -- Zimbabwe -- Rhodes Matopos National Park; Bushbuck -- Zimbabwe -- Rhodes Matopos National Park; Greater kudu -- Zimbabwe -- Rhodes Matopos National Park